Pla Crystallization Kinetics and Morphology Development - Siginer, D (Walter de Gruyter GmbH, 2018)
This paper investigates the crystallization kinetics and morphology development of PLA. The transitory stages in the evolving flow-induced crystallization of PLA are identified and classified in terms of the overall crystallization kinetics and the crystalline morphologies. Under quiescent conditions, temperature governs the crystallization process and the slow crystallization kinetics of PLA is highlighted under these conditions, whereas under shearing conditions, the crystallization is highly enhanced due to the promotion of the nucleation mechanism. The enhancement of the crystallization implies also morphological modifications. Depending on the shear rate and the shearing time the microstructure changes dramatically: spherulitic microstructure, fine grained microstructure and oriented microstructure. For a specific shear rate, depending on the magnitude of the shearing time the microstructure assumes the following states: for low shearing time only an increase of the number of nuclei is observed (leading to fine grained microstructure), followed by a saturation of point-like nuclei, and for a relatively long shearing time (i. e. beyond a critical shearing time) the development of oriented structures looking like "shish-kebabs"is observed. The critical shearing time for the formation of oriented structures in PLA is determined as a function of the shear rate. © 2018, Carl Hanser Verlag, Munich.